Analisa Dampak Bayangan Modul Terhadap Output PLTS - Adrian Mansur (Energi & Kelistrikan, 2019)
Solar cells are a technology that converts sunlight into electricity, therefore if there is a shadow that covers the surface of the module it will cause a decrease in energy production, therefore this study aims to see the impact of shadows on the module by analyzing the output per PLTS array, then the shadow source removed. The analysis shows that there is an increase in output at 06.00-12.00 in array 2 by 48% above the increase in average output which is only around 24%, as well as in the output style that is not far adrift from other arrays with only 1 % deviation remaining At 12.00-18.00 changes in output can also be observed in Array 4 by 46% above the average increase of only 39%, as well as the output style with a deviation from 21% to 1%.